1998
DOI: 10.1016/s0022-5223(98)70251-x
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of continuous hyperpolarized arrest with pinacidil over St. Thomas' hospital solution during prolonged ischemia

Abstract: Myocardial protection during a longer, more clinically relevant ischemic period is feasible with a potassium channel opener only when it is given continuously. Continuous low-flow pinacidil cardioplegia was superior to St. Thomas' Hospital solution given either as an intermittent or continuous infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…These potassium-channel openers have been shown to be superior or equivalent to depolarized arrest during both short and long periods of global ischemia. [5][6][7] Other laboratories have corroborated our findings that hyperpolarized arrest may be superior to depolarized arrest for myocardial protection. 8,9 Recently, we have shown that ATP-sensitive potassium-channel openers prevent intracellular calcium accumulation during global ischemia.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…These potassium-channel openers have been shown to be superior or equivalent to depolarized arrest during both short and long periods of global ischemia. [5][6][7] Other laboratories have corroborated our findings that hyperpolarized arrest may be superior to depolarized arrest for myocardial protection. 8,9 Recently, we have shown that ATP-sensitive potassium-channel openers prevent intracellular calcium accumulation during global ischemia.…”
supporting
confidence: 83%
“…Our laboratory has proposed that adopting an alternative strategy of hyperpolarized arrest may alleviate many of these untoward sequelae. [5][6][7] To hyperpolarize the cell membrane, we have administered drugs that open ATP-sensitive potassium channels. These potassium-channel openers have been shown to be superior or equivalent to depolarized arrest during both short and long periods of global ischemia.…”
mentioning
confidence: 99%
“…Although this blood-perfused model offers a closer approximation to the clinical scenario than a crystalloid perfused one, care should be taken in extrapolating results from the present study to the clinical setting, as shown in a blood-perfused, parabiotic, isolated rabbit heart model (6,7,9,15). To determine the clinical feasibility of nicorandil cardioplegia, in vivo studies are clearly needed.…”
Section: Discussionmentioning
confidence: 98%
“…This process was proposed as a preservation of energy. 6 PCOs have been shown to reduce infarct size, attenuate myocardial stunning, and ameliorate reperfusion injury. 7 Another advantage of PCOs may be their ability to prevent the cell swelling which has been implicated as a cause in ischemic injury.…”
Section: Discussionmentioning
confidence: 99%